Tiger eyes - Blume, Judy. (New York Delacorte Press, 2013)
Resettled in the "Bomb City" with her mother and brother, Davey Wexler recovers from the shock of her father's death during a holdup of his 7-Eleven store in Atlantic City.
"Special edition Behind the scenes with Judy"-- Cover.
Includes a "Behind the scenes with Judy" section on the making of the motion picture based on the book.
Originally published: Scarsdale, N.Y. : Bradbury Press, 1981.
Has appeared on lists of banned or challenged books compiled by the American Library Association since 1990 to inform the public about censorship efforts that affect libraries and schools.
Keywords: Death -- Fiction; Fathers -- Death -- Fiction; Bereavement in adolescence -- Fiction; Bereavement in adolescence -- Juvenile fiction; Families -- Fiction; New Mexico -- Fiction